ADVANCED MATHEMATICS FORM 5 – TRIGONOMETRY

Share this post on:

APPLICATIONS OF PYTHAGORAS IDENTITY

I.                 SOLVING TRIG EQUATIONS

Example 1.

Solve the equation 1 + edu.uptymez.comedu.uptymez.com= 0 for the values of the values (θ) between 00 and 3600 inclusive.

Solution:

1 + edu.uptymez.comedu.uptymez.com=0

But from Pythagoras identity

edu.uptymez.com

cosθ = 0,cos θ =-1
case of cosθ = 0
θ=cos(0)
θ=90

θ=900,2700

              edu.uptymez.com
Example 2.

Solve for the values of x between 00 and 3600 inclusive of

(i)                           Tan 4x + 7 = 4sec2x

(ii)                        -6sm2x – cosx + 5 =0

Solution

Tan4x + 7 =4sec2x

But tan2x + 1 =sec2x

Tan4x + 7=4(tan2x + 1)

Tan4x + 7 =4tan2x + 4

Tan4x +7-4tan2x  -4 =0

Tan4x -4tan2x + 3 =0

Let tan2x =m

Then m2 – 4m +3 =0

          m2 -3m –m + 3 =0

          m(m -3)-1(m-3)=0

         (m – 1)(m-3) =0

         m – 1 =0, m- 3=0

          m= 1, m=3

Case 1  m =1 =tan2x

              Tan x = edu.uptymez.com

              Tan x = 1

              X = tan-1(1) = 450

              X = 1800 + 450 = 2250

              Tan x =-1

              X= tan -1(-1)

              X =180 450 =1350

              X = 3600 -450=3150

Case 2: m3

Tan2x = 3, tanx=edu.uptymez.comedu.uptymez.com

Tan x =edu.uptymez.com

X = tan-1(edu.uptymez.com =600

X =1800 + 600 =2400

tan x =-edu.uptymez.com

x = tan -1(-edu.uptymez.com

= 1800 -600=1200

X=3600 -600=3000

edu.uptymez.comx=edu.uptymez.com work on (ii)

II PROVING IDENTITIES

Examples: prove the following identify

 i)                  Tan2θ + sin2θ =(secθ + cosθ) (secθ – cosθ)

 ii)                Cot4θ + cot2θ =cosec4θ – cosec2θ

 iii)             edu.uptymez.com= cosecθ – cotθ

iv)              edu.uptymez.com

v)                cosecθ –sinθ = cotθ

Solution: (i)
tan2θ + sin2θ = (secθ+ cosθ) (secθ –cosθ)

Delaying with R.H.s

Proof = (secθ + cosθ)(secθ – cosθ)

Then

=sec2θ – cos2θ

But sec2θ = 1+ tan2θ and

Cos2θ = 1 –sin2θ
=1 + tan2θ -(1 – sin2θ)
=1 + tan2θ -1 + sin2θ

 =tan2θ+ sin2θ
edu.uptymez.comtan2θ+ sin2θ L.H.S proved


ii) cot4θ+ cot²θ= cosec4θ – cosec2θ

solution.
Dealing with L.H.S

 Proof

        =Cot4θ + cot2θ
then

 =Cot2θ(cot2θ + 1)

 But Cot2θ+ 1 =cosec2θ
Cot2θ =cosec2θ -1
(cosec2θ -1) cosec2θ
Cosec4θ – cosec2θ R.H.S
edu.uptymez.comCot4θ + cot2θ= cosec4θ – cosec2θ

edu.uptymez.com

iv) sin θtanθ + cosθ=secθ

solution.

Proof

Dealing with L.H.S

Sinθtanθ+ cosθ

But tanθ = edu.uptymez.com

Then

Sinθ edu.uptymez.com+ cosθ

edu.uptymez.com= edu.uptymez.com= secθ

sin²θ + cos²θ =1 (Pythagoras identity)

edu.uptymez.comsinedu.uptymez.com

edu.uptymez.com

III)      ELIMINATION PROBLEMS
Examples:

Eliminate ÆŸ from the following equations

i)                  Cosθ + 1 =x and sinθ =y

ii)                X= a sinθ and y= btan θ

iii)             X= 1 + tanθ and y = cos θ

iv)              X= sinθ – cosθ

Y= cotθm+ tanθ

Solution.
(i) Cosθ + 1 =x

Cosθ=x – 1 ……… (i)

sinθ = y…………..(ii)

squaring equations (i) and (ii) the sum

cos²θ+ sin²θ= (x -1)² + y²

but sin²θ + cos²θ =1

then 1= (x – 1)² + y²

1 = x² – 2x + 1 + y²

x² + y2 -2x + 1 – 1 =0

x² +y²- 2x =0

ii) from x = a sinθ, sinθ=edu.uptymez.com

and from y=btanθ, tanθ=edu.uptymez.com

refer edu.uptymez.com+ edu.uptymez.com=1

dividing by edu.uptymez.comboth sides

edu.uptymez.com+ edu.uptymez.com= edu.uptymez.com

1+ edu.uptymez.com=edu.uptymez.com

But edu.uptymez.com

Then 1 + edu.uptymez.com= edu.uptymez.com

edu.uptymez.com

1 + edu.uptymez.com= edu.uptymez.com

1 + edu.uptymez.com= edu.uptymez.com

edu.uptymez.com

iii) X = 1 + edu.uptymez.com

edu.uptymez.com= x – 1 ……….. (i)

edu.uptymez.com= y

Refer, edu.uptymez.com+ edu.uptymez.com= 1

Dividing by edu.uptymez.comboth sides

edu.uptymez.com+ edu.uptymez.comedu.uptymez.com

edu.uptymez.comÆŸ + 1 = edu.uptymez.com

edu.uptymez.com+ 1= edu.uptymez.com

edu.uptymez.com+ 1 = edu.uptymez.com

edu.uptymez.com= 1

Solution (iv)
x =edu.uptymez.comedu.uptymez.com ………….(a)

Y =edu.uptymez.com + edu.uptymez.com……….(b)

From (b) edu.uptymez.comedu.uptymez.com

= edu.uptymez.com+ edu.uptymez.com

Y=edu.uptymez.com =edu.uptymez.com

Y =edu.uptymez.com

Squaring

x² = edu.uptymez.com

x² = edu.uptymez.com-2edu.uptymez.com+ edu.uptymez.com

=edu.uptymez.com+ edu.uptymez.com-2edu.uptymez.com

x² = 1- 2edu.uptymez.com

then

x² = 1 – 2edu.uptymez.com

but edu.uptymez.com=edu.uptymez.com

x² = 1 – 2edu.uptymez.com

x² =1 – edu.uptymez.com

x² + edu.uptymez.com-1 =0

NB: In elimination problems concept is to eliminate the trig function in the equation, then try the possibilities of eliminating it by connecting it to the pythageras theorem (identity)

COMPLEMENTARY ANGLES

Consider the triangle below

edu.uptymez.com

edu.uptymez.com= edu.uptymez.com(i) edu.uptymez.comedu.uptymez.com (iv)

edu.uptymez.com= edu.uptymez.com(ii) edu.uptymez.com=edu.uptymez.com (v)

edu.uptymez.com=edu.uptymez.com (iii) edu.uptymez.com= edu.uptymez.com.(vi)

Thus

edu.uptymez.com

Is the condition for complementary angles

Definition: Complementary angles are angles whose sum is 90°

E.g: A + B = 90°

         30° + 60° = 90°

30° and 60° are complementary angles.

NB: Supplementary angles are angles whose sum is 180°

Eg: A + B = 180°

Then A and B are supplementary angles

COMPOUND ANGLES FORMULA

Consider two angles say A and B then the angles A + B are called compound angles.

 The concept here is to obtain

Sin (A ±B), Cos (A ±B), Tan (A ± B)

However it is easier to say that

Sin(A + B) = sin A + sin B

Testing if it is true

Let A= 60 and B= 30°

Sin(A + B) = sin(60° + 30°) = sin 90° = 1

Sin A + sin B = sin 60°+ sin 30°

edu.uptymez.com

 

Consider the figure below

edu.uptymez.com

From edu.uptymez.comOTR

edu.uptymez.com= edu.uptymez.com

But TR = TS + SR

edu.uptymez.com= edu.uptymez.com

=edu.uptymez.com + edu.uptymez.com, but TS = PQ

=edu.uptymez.com + edu.uptymez.com

Multiplying edu.uptymez.comby edu.uptymez.comand edu.uptymez.comby edu.uptymez.com

edu.uptymez.com

But from the figure above

edu.uptymez.com= edu.uptymez.com= edu.uptymez.com

edu.uptymez.com= edu.uptymez.com, edu.uptymez.com=edu.uptymez.com

Then substituting into

edu.uptymez.com=edu.uptymez.com + edu.uptymez.com

edu.uptymez.comedu.uptymez.com

From (1) if B=B
edu.uptymez.com
But edu.uptymez.com=edu.uptymez.com

edu.uptymez.com=⁻edu.uptymez.com

edu.uptymez.com

 Again from the figure above edu.uptymez.com

edu.uptymez.com=edu.uptymez.com

But OT = edu.uptymez.comedu.uptymez.com

edu.uptymez.com
edu.uptymez.com

edu.uptymez.com

For tan edu.uptymez.com

Refer edu.uptymez.com=edu.uptymez.com

edu.uptymez.com=edu.uptymez.com

edu.uptymez.com


Dividing numeration and denomination by edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com=edu.uptymez.com

From above equation

If B = -B, then

Tan( A+edu.uptymez.com = edu.uptymez.com

But tanedu.uptymez.com=⁻ tanB

edu.uptymez.com=edu.uptymez.com

Or, shown by

edu.uptymez.com= edu.uptymez.com

Use procedure (5) obtain (6)

APPLICATION OF THE COMPOUND FORMULAE

I.                 PROVING OF IDENTITIES

Examples:

Prove the following trig identities

i)                  edu.uptymez.com= edu.uptymez.com+ edu.uptymez.com

ii)                edu.uptymez.com=edu.uptymez.com

iii)             edu.uptymez.com=edu.uptymez.com

Proof(i) edu.uptymez.com=edu.uptymez.com

Dealing with L.H.S

edu.uptymez.com

II.               COS(A+B)COS(A-B) =edu.uptymez.com

Proof dealing with L.H.S edu.uptymez.com

edu.uptymez.com

edu.uptymez.comB – edu.uptymez.com

edu.uptymez.com=1- edu.uptymez.comand

edu.uptymez.com= 1 –edu.uptymez.com then

edu.uptymez.comedu.uptymez.com

edu.uptymez.comedu.uptymez.comedu.uptymez.com -(sin2A-cos2Asin2B)
cos2A-cos2Asin2B-sin2A+cos2Asin2B

edu.uptymez.comedu.uptymez.comR.H.S

edu.uptymez.comedu.uptymez.comedu.uptymez.com=edu.uptymez.comedu.uptymez.com

III.           edu.uptymez.com=edu.uptymez.com

Proof

Dealing with L.H.S

edu.uptymez.com=edu.uptymez.com

edu.uptymez.com=1

=edu.uptymez.com

But edu.uptymez.com= edu.uptymez.com

=edu.uptymez.com + 1

1 – edu.uptymez.com

=edu.uptymez.com

edu.uptymez.com

edu.uptymez.comedu.uptymez.com=edu.uptymez.com

IV.         FINDING VALUES OF TRIG RATIOS

Examples: Evaluate

a)    edu.uptymez.comb) edu.uptymez.comc) edu.uptymez.comd) edu.uptymez.com

Solution:
a) edu.uptymez.com= edu.uptymez.com

=edu.uptymez.comedu.uptymez.com

edu.uptymez.com 

edu.uptymez.comedu.uptymez.com=edu.uptymez.com

edu.uptymez.comedu.uptymez.com=edu.uptymez.com

= edu.uptymez.com

edu.uptymez.com= 1

edu.uptymez.com=edu.uptymez.com

edu.uptymez.com= edu.uptymez.com= edu.uptymez.com

edu.uptymez.com= edu.uptymez.com

edu.uptymez.com= edu.uptymez.com

=edu.uptymez.comedu.uptymez.com

edu.uptymez.com

edu.uptymez.comedu.uptymez.com= edu.uptymez.com

edu.uptymez.com.
If edu.uptymez.com= edu.uptymez.com, find the tangent of x in terms of edu.uptymez.comand edu.uptymez.comthen find tan x when edu.uptymez.com= 45° and edu.uptymez.com= 60° (leaving your answer in surd form)

edu.uptymez.com: edu.uptymez.com= cosedu.uptymez.com

edu.uptymez.com+ edu.uptymez.com= edu.uptymez.com+ edu.uptymez.com

edu.uptymez.comedu.uptymez.com=cos x cosedu.uptymez.comedu.uptymez.com sinedu.uptymez.com

edu.uptymez.com=edu.uptymez.com

edu.uptymez.com= edu.uptymez.com

edu.uptymez.com=edu.uptymez.com = edu.uptymez.com

edu.uptymez.com=edu.uptymez.com

Given edu.uptymez.com=45°, edu.uptymez.com= 60edu.uptymez.com

edu.uptymez.com= edu.uptymez.com

edu.uptymez.com

edu.uptymez.comedu.uptymez.com= edu.uptymez.com

DOUBLE ANGLE FORMULAE

Recall (a) edu.uptymez.com=edu.uptymez.com

If B = A

edu.uptymez.com= edu.uptymez.com

edu.uptymez.com=2edu.uptymez.com

edu.uptymez.com

b)   edu.uptymez.com

If B = A

edu.uptymez.com

= edu.uptymez.com

edu.uptymez.comedu.uptymez.com

c)    edu.uptymez.com

If B = A

edu.uptymez.com

edu.uptymez.com=edu.uptymez.com ………………….. (iii)


Also from

edu.uptymez.com=edu.uptymez.comedu.uptymez.com

But edu.uptymez.com= 1 –edu.uptymez.com

edu.uptymez.com=(1 –
edu.uptymez.com)- edu.uptymez.com
= 1 –
edu.uptymez.comedu.uptymez.com
edu.uptymez.com

Or
edu.uptymez.com= edu.uptymez.comedu.uptymez.com

edu.uptymez.com= 1 – edu.uptymez.com

edu.uptymez.com =edu.uptymez.com

            = edu.uptymez.com– 1 + edu.uptymez.com

edu.uptymez.com= 2edu.uptymez.com – 1

edu.uptymez.com


TRIPLE ANGLE FORMULAE

i)                  Consider edu.uptymez.com

sin(2θ+θ) =sin2θcosθ +edu.uptymez.com

edu.uptymez.com= 2edu.uptymez.com

edu.uptymez.com=edu.uptymez.comedu.uptymez.com

edu.uptymez.com= 2edu.uptymez.com

= 2edu.uptymez.com + edu.uptymez.comedu.uptymez.com

                         edu.uptymez.com3edu.uptymez.comedu.uptymez.com


But edu.uptymez.comθ = 1 –edu.uptymez.com

                                = edu.uptymez.comedu.uptymez.com

                                 = 3edu.uptymez.comθ – edu.uptymez.com

                                 =3edu.uptymez.com – 4edu.uptymez.com

edu.uptymez.com

ii)                Consider edu.uptymez.com= edu.uptymez.com

=edu.uptymez.comedu.uptymez.com

But edu.uptymez.com= edu.uptymez.comedu.uptymez.com

edu.uptymez.com= 2edu.uptymez.com

=edu.uptymez.comedu.uptymez.com

edu.uptymez.com-2edu.uptymez.com

edu.uptymez.com=cos3θ

But edu.uptymez.com=1 –edu.uptymez.com

edu.uptymez.com– 3edu.uptymez.com

edu.uptymez.com+3edu.uptymez.com

edu.uptymez.com

iii)             Consider edu.uptymez.com

edu.uptymez.com=edu.uptymez.com

edu.uptymez.com

But edu.uptymez.com= edu.uptymez.com

edu.uptymez.com

=edu.uptymez.com

edu.uptymez.com

=edu.uptymez.com

edu.uptymez.com

Alternative: Using edu.uptymez.com=edu.uptymez.com

edu.uptymez.com

Dividing by cos3θ numerator and denominator

 edu.uptymez.com

edu.uptymez.com

Share this post on: